The Effect of Investment Decisions, Dividend Policy, and Earnings Per Share on the Value of The Companies In The Lq45 Index - Nadia Apriana; Ari Agung Nugroho; Sumar Sumar (Garuda Prestasi Nusantara Consulting, 2022)
This study aims to determine the effect of investment decisions, dividend policy, and earnings per share on the value of companies incorporated in the LQ45 index for the 2017-2020 period. This research is a type of quantitative research. The population in this study amounted to 66 companies, using purposive sampling technique, the research sample obtained was 17 companies. The analytical method used in this research is multiple linear regression. The results of the study show that: (1) investment decisions have a positive effect on firm value. (2) Dividend policy has a positive effect on firm value. (3) Earning per share has no effect on firm value. Keywords: Investment Decision (PER), Dividend Policy (DPR), Earning Per Share (EPS), and Company Value(PBV)